Treating Wet Oil in Amara Oil Field Using Nanomaterial (SiO2) With Different Types of De emulsifiers - Alkarbalaee, Ayat Ragheb; Hammadi, Adel Sharif; Abdul Majeed, Ghassan Hamid (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
One of the most important problems in the oil production process and when its continuous flow, is emulsified oil (w/o emulsion), which in turn causes many problems, from the production line to the extended pipelines that are then transported to the oil refining process. It was observed that the nanomaterial (SiO2) supported the separation process by adding it to the emulsion sample and showed a high separation rate with the demulsifiers (RB6000) and (sebamax) where the percentage of separation was greater than (90 and 80 )% respectively, and less than that when dealing with (Sodium dodecyl sulfate and Diethylene glycol), the percentage of separation was (60% and 50%) respectively. The high proportion of (NaCl + distilled water) raises the probability of the separation efficiency as the separation was (88.5,79)% and (65.5, 55) % for (RB6000, SebaMax)respectively with (SiO2) at 70 °C, while the results of separation were (77,85)% and (65,40) for (RB6000, Seba Max) respectively with (SiO2) at 50 °C after 120 minutes, where the (w/o ratio) was (9:1) for the high separation results and (7:3) for the lower separation results, at a speed of (12000rpm), and with a salt concentration of (1500) ppm, and less of these results at lower volumetric and temporal conditions. The (NaCl) salt deals with the wall films separating the droplets and reduces their viscosity [1]. As for the pH factor, it is at the value (2 and 3) represent a stable emulsion that is difficult to separate easily, but with the passage of raising the pH away from the acidic medium and near to the basic direction, a significant increase in the separation process was observed compared with the acidic medium at lower values, after 120 minutes the separation seemed to be good efficient, reaching (60 and 70) % respectively, while at the same time the emulsion reached a more efficient separation level with a pH of ( 8 and 7) equal to (80 and 87.3) %, at 50 °C with SebaMax demulsifier in presence of (SiO2), and with the same pH values, an increase was observed in the separation with the increase in temperature to (70 °C), then it returns to be a reverse emulsifier when the value exceeds (10) to (11, 12, 13).